Elektra Kft. avagy: bevezetés a kapitalizmus politikai gazdaságtanába - Schiffer, Pál (Hungary : Budapest Filmstúdió Kft, 1995)
The ironic subhead of the film covers a harsh reality. Six workers, once employees of Videoton, decide to try to help themselves by founding a joint venture ... That's why they form ELEKTRA Ltd. Time will pass and the business will become a capitalist company step by step. And the members, once formed on the basis of solidarity, learn for themselves what capitalism is.
Keywords: Documentary films